EU TRADEMARKS FOR WINE WHICH CONTAINS INDICATIONS OF GEOGRAPHICAL ORIGIN - Lučić, Sonja (Economics of Agriculture, 2018)
Trademarks and indications of geographical origin have different legal nature. Main difference is that trademarks indicate origin of goods from specifc business entity and indications of geographical origin refers to geographical origin of goods. In an effort to fnd suitable forms of labelling their product, manufacturers are also using indications of geographical origin. In other words, beside the difference that exists between trademarks and indications of geographical origin, in practice there are cases when indications of geographical origin is used as subject of submitted or registered trademark. Registration practice of indications of geographical origin as trademarks is very restrictive today and it is allowed only under special conditions. In this work we will analyze connection between indications of geographical origin for wines related to the EU trademark in the light of the current EU regulations and most recent practice of the Court of Justice of the European Union.